User-assisted sparse stereo-video segmentation - KOKARAM, ANIL; PITIE, FRANCOIS (My University, 2013)
User-assisted Sparse Stereo-video Segmentation Félix Raimbault, François Pitié and Anil Kokaram Sigmedia Group Dept. of Electronic and Electrical Engineering Trinity College Dublin, Ireland {raimbauf, fpitie, anil.kokaram}@tcd.ie ABSTRACT Motion-based video segmentation has been studied for many years and remains challenging. Ill-posed problems must be solved when seeking for a fully automated solution, so it is increasingly popular to maintain users in the processing loop by letting them set pa- rameters or draw mattes to guide the segmentation process. When processing multiple-view videos, however, the amount of user in- teraction should not be proportional to the number of views. In this paper we present a novel sparse segmentation algorithm for two- view stereoscopic videos that maintains temporal coherence and view consistency throughout. We track feature points on both views with a generic tracker and analyse the pairwise affinity of both tem- porally overlapping and disjoint tracks, whereas existing similar techniques only exploit the information available when tracks over- lap. The use of stereo-disparity also allows our technique to process jointly feature tracks on both views, exhibiting a good view consis- tency in the segmentation output. To make up for the lack of high level understanding inherent to segmentation techniques, we allow the user to refine the output with a split-and-merge approach so as to obtain a desired view-consistent segmentation output over many frames in a few clicks . We present several real video examples to illustrate the versatility of our technique.
ACM International Conference Proceeding Series
ACM International Conference
PUBLISHED
Keywords: Motion-based video segmentation; Motion-based video segmentation